2021
DOI: 10.3389/fpls.2021.721631
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Heterosis for Yield Influencing Traits in Brassica juncea Using a Doubled Haploid Population and Its Backcross Progenies

Abstract: The exploitation of heterosis through hybrid breeding is one of the major breeding objectives for productivity increase in crop plants. This research analyzes the genetic basis of heterosis in Brassica juncea by using a doubled haploid (DH) mapping population derived from F1 between two heterotic inbred parents, one belonging to the Indian and the other belonging to the east European gene pool, and their two corresponding sets of backcross hybrids. An Illumina Infinium Brassica 90K SNP array-based genetic map … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…EH2 and PJK belong to distinct Indian and East European gene pools, respectively 2 . These gene pools are heterotic, and therefore have significant application in hybrid breeding in B. juncea 72 . The QTLs for seed size, coat color, oil content, and other seed traits have been previously reported in B. juncea 2 , 11 , 28 , 73 .…”
Section: Discussionmentioning
confidence: 99%
“…EH2 and PJK belong to distinct Indian and East European gene pools, respectively 2 . These gene pools are heterotic, and therefore have significant application in hybrid breeding in B. juncea 72 . The QTLs for seed size, coat color, oil content, and other seed traits have been previously reported in B. juncea 2 , 11 , 28 , 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Immortalized BC population with one parental line has only two genotypes at each locus, and therefore cannot provide the full information to estimate the dominant effect. However, when used together, immortalized BC populations at both directions to the original two parental lines can also be used in investigating the genetic basis of heterosis (Li et al, 2008b;Aakanksha et al, 2021). GAHP is freely available from https://isbreeding.caas.cn.…”
Section: Applications Of the Gahp Software Package In Genetic Studiesmentioning
confidence: 99%
“… Li et al (2008b) reported two immortalized BC populations in rice and used them to identify the main-effect QTLs and digenic epistatic loci underlying the heterosis of agronomic and economic traits. Aakanksha et al (2021) investigated the heterosis on yield in Brassica juncea by using a DH and two-directional immortalized BC populations. Li et al (2018) developed two-directional immortalized BC populations and one immortalized F 2 population, and used them to detect QTLs affecting fiber quality traits in upland cotton.…”
Section: Introductionmentioning
confidence: 99%
“…A SNP array-based genetic map was used to identify 695 QTL for 14 traits, including PA, flowering, silique and other seed-related traits, in B. juncea . It also showed that epistasis among loci plays an important role in controlling heterosis in yield of B. juncea [ 98 ].…”
Section: Underlying Genetics Dictate Plant Yieldmentioning
confidence: 99%